Expectativas para que México cambie el destino de sus exportaciones; Expectations for Mexico to change the destination of its exports - Sergio Lagunas Puls; Carmen Lilia Cervantes Bello (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2019)
– This article analyses the Mexican exports to China and the European Union along with the effects of a possible shift of Mexican products to the above markets due to a change within the US-Mexico trade agreements. Beginning with a review of Mexican trade agreements with the European Union and China, the article describes the quarterly Mexican exports of goods and products and their primary destinations to these countries. Later, the paper analyses the exports of Mexican products from years 2012-2015 fitting their values to Gamma and Normal distributions. Probabilities for different scenarios, which include the average and maximum exports, are given in order to quantify the possibilities that Mexico has to replace the goods and products that can not be positioned in the American market.
urn:cuant:es:0000-rmce.v28i0.27813
Keywords: F17; F15; C16; C13; 330; Mexican export; probability; European Union